Bonded neodymium-iron-boron magnet and preparation method and application thereof
By introducing semi-metallic ferrous magnets as reinforced phases into the bonded NdFeB magnets, the problem of difficult to take into account both mechanical strength and magnetic properties in the prior art is solved, and the synchronous improvement of high mechanical strength and excellent magnetic properties is achieved.
Patent Information
- Application Number
- CN202411690243.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
The existing bonded NdFeB magnets are difficult to maintain excellent magnetic properties while increasing mechanical strength, and require high temperatures to increase energy consumption during the preparation process.
The semi-metallic ferrous magnet is introduced into the bonded NdFeB magnet as the reinforcement phase, and by adjusting its mass ratio, the mechanical strength and magnetic properties are improved.
The synchronous improvement of the mechanical strength and magnetic properties of the bonded NdFeB magnet is achieved, reducing the energy consumption of the preparation process.
Smart Images

Figure BDA0005150751070000141 
Figure BDA0005150751070000151
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnetic materials, and specifically relates to a bonded NdFeB magnet, and in particular to a bonded NdFeB magnet and a preparation method and application thereof. Background Art
[0002] With the rapid development of new energy vehicles and the massive expansion of motor business, bonded NdFeB magnets that can be formed in one go and made into various shapes have been vigorously developed and widely used in motors of new energy vehicles. However, the low mechanical strength of bonded NdFeB magnets limits the application scope of bonded NdFeB magnets.
[0003] CN102938283A discloses a high-magnetism and high-mechanical-strength bonded NdFeB permanent magnet and a preparation method thereof. The NdFeB permanent magnet is made by compounding metallocene polymer ferromagnetic powder as a binder, stainless steel powder as a mechanical strength enhancer and rapidly quenched NdFeB magnetic powder, and has the characteristics of strong magnetism, high mechanical strength, small dimensional tolerance, wide application, convenience for subsequent rolling and grinding, low loss in finished product transportation and assembly, and long service life.
[0004] CN106816251A discloses a high-performance bonded NdFeB magnet and a preparation method thereof. By adding a suitable amount of nano-ceramics, nano-TiO2, and nano-zinc oxide whiskers to the resin phase and rationally allocating the amount of magnetic powder and resin, the mechanical strength of the magnet, such as impact strength and tensile strength, is greatly improved, and the magnet has better processing performance, with little dimensional change during processing, and is easy to be processed into products with high dimensional accuracy.
[0005] CN106384639A discloses a method for preparing a high-performance bonded NdFeB permanent magnet material. A low-melting-point metal or alloy film is coated on the surface of a rapidly quenched NdFeB powder by a vapor deposition method, and then vacuum hot-pressed at a temperature 0.85-0.95 times the melting point of the metal or alloy. The metal or alloy softens and has good ductility, acting as a binder, and finally a high-strength and high-magnetic-performance bonded NdFeB magnet is obtained.
[0006] In the prior art, reinforcing phases are often added to bonded NdFeB magnets to improve their mechanical strength, but the added stainless steel powder or ceramic powder is a non-magnetic material, which affects the magnetic properties of the bonded NdFeB magnets. The alloy coating technology requires a higher temperature, which greatly increases the energy consumption of preparation.
[0007] Therefore, it is of great significance to develop a material with both high mechanical strength and excellent magnetic properties. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a bonded NdFeB magnet and its preparation method and application. The present invention introduces a semi-metallic ferrimagnet with obvious energy absorption advantages and high magnetocrystalline anisotropy as a reinforcement phase into the bonded NdFeB magnet, thereby improving the mechanical strength of the bonded NdFeB magnet and improving the magnetic properties of the bonded NdFeB magnet.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a bonded NdFeB magnet, comprising NdFeB powder and semi-metallic ferrimagnet powder.
[0011] The mass ratio of the NdFeB powder to the semi-metallic ferrimagnetic powder is 100:(3-15).
[0012] The present invention adopts semi-metallic ferrimagnetic powder with a specific mass ratio as a reinforcing phase. On the one hand, the semi-metallic ferrimagnetic powder belongs to a cubic crystal system, has good energy absorption performance, and can improve the mechanical strength of the bonded NdFeB magnet; on the other hand, the semi-metallic ferrimagnetic powder has high magnetocrystalline anisotropy, and the spin polarization rate at the Fermi level is 90%-99%, which improves the mechanical strength of the bonded NdFeB magnet while improving the magnetic properties of the bonded NdFeB magnet.
[0013] In the present invention, the mass ratio of NdFeB powder to semi-metallic ferrimagnetic powder is 100:(3-15), for example, it can be 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:11, 100:12, 100:13, 100:14 or 100:15, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0014] Preferably, the semi-metallic ferrimagnetic powder comprises perovskite semi-metallic ferrimagnetic powder.
[0015] In the present invention, the raw materials of the perovskite semi-metallic ferrimagnetic powder are easy to obtain, and the production process is relatively simple. The perovskite semi-metallic ferrimagnetic powder belongs to the cubic crystal system, has a cubic structure with Fm3m symmetry, has excellent mechanical strength, and has high energy absorption performance, further improving the mechanical properties of the bonded NdFeB magnet.
[0016] Preferably, the perovskite semi-metallic ferrimagnetic powder comprises any one of Pb2CrReO6, Ba2FeReO6 or Sr2FeReO6 or a combination of at least two thereof. Typical but non-limiting combinations include Pb2CrReO6 and Ba2FeReO6, Pb2CrReO6 and Sr2FeReO6, Ba2FeReO6 and Sr2FeReO6, and Pb2CrReO6, Ba2FeReO6 and Sr2FeReO6.
[0017] Preferably, the perovskite semi-metallic ferrimagnetic powder is Pb2CrReO6.
[0018] Preferably, the D of the NdFeB powder is 50 The particle size is 30-60 μm, for example, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm, 50 μm, 52 μm, 54 μm, 56 μm, 58 μm or 60 μm, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable. Preferably, it is 30-45 μm.
[0019] In the present invention, the D of the semi-metallic ferrimagnetic powder is 50 A particle size that is too large is not conducive to full filling of perovskite magnetic powder, while a particle size that is too small reduces the magnetic permeability and slows the saturation magnetization speed.
[0020] Preferably, the D of the semi-metallic ferrimagnetic powder is 50 The particle size is 15-25 μm, for example, it can be 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the mass ratio of the NdFeB powder to the semi-metallic ferrimagnetic powder is 100:(5-10), for example, it can be 100:5, 100:5.5, 100:6, 100:6.5, 100:7, 100:7.5, 100:8, 100:8.5, 100:9, 100:9.5 or 100:10, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the NdFeB magnet also includes a binder and a lubricant.
[0023] Preferably, the adhesive comprises a thermosetting epoxy resin and a curing agent.
[0024] Preferably, the thermosetting epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol S epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, novolac epoxy resin, brominated epoxy resin, glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin or alicyclic epoxy resin.
[0025] Preferably, the thermosetting epoxy resin comprises bisphenol A type epoxy resin.
[0026] The degree of polymerization of thermosetting epoxy resin will affect the state of epoxy resin at room temperature. If the degree of polymerization is low, it will be liquid, which is not conducive to subsequent operations; if the degree of polymerization is too high, it will be solid and have high hardness, which will destroy the magnet structure.
[0027] Preferably, the degree of polymerization of the thermosetting epoxy resin is 10-20, for example, the degree of polymerization may be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the curing agent comprises any one of m-phenylenediamine, ethylenediamine or polyamide or a combination of at least two thereof, typical but non-limiting combinations include phenylenediamine and ethylenediamine, phenylenediamine and polyamide, ethylenediamine and polyamide, and phenylenediamine, ethylenediamine and polyamide, preferably m-phenylenediamine.
[0029] Preferably, the lubricant comprises any one or a combination of at least two of olive oil, graphite or oxidized polyethylene wax. Typical but non-limiting combinations include olive oil and graphite, olive oil and oxidized polyethylene wax, graphite and oxidized polyethylene wax, and olive oil, graphite and oxidized polyethylene wax, preferably graphite.
[0030] In the bonded NdFeB magnet, the mass ratio of the NdFeB powder to the binder is 100:(2-7), for example, it can be 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5, 100:5, 100:5.5, 100:6, 100:6.5 or 100:7, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 100:(3-5.5).
[0031] Preferably, the mass ratio of the NdFeB powder to the lubricant is 100:(0.5-1), for example, it can be 100:0.5, 100:0.55, 100:0.6, 100:0.65, 100:0.7, 100:0.75, 100:0.8, 100:0.85, 100:0.9, 100:0.95 or 100:1, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the mass ratio of the thermosetting epoxy resin to the curing agent in the adhesive is 1:(0.1-0.2), for example, it can be 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19 or 1:0.2, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] In a second aspect, the present invention provides a method for preparing the bonded NdFeB magnet as described in the first aspect, the preparation method comprising:
[0034] The magnetic powder is mixed with the binder and dried to obtain NdFeB magnet powder; the NdFeB magnet powder is pressed to obtain a NdFeB magnet green body; and the NdFeB magnet green body is solidified to obtain the bonded NdFeB magnet.
[0035] The magnetic powder includes neodymium iron boron powder and semi-metallic ferrimagnetic powder.
[0036] Preferably, the adhesive comprises a thermosetting epoxy resin and a curing agent.
[0037] Preferably, the mass ratio of the thermosetting epoxy resin to the curing agent in the adhesive is 1:(0.1-0.2), for example, it can be 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19 or 1:0.2, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the thermosetting epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol S epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, novolac epoxy resin, brominated epoxy resin, glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin or alicyclic epoxy resin.
[0039] Preferably, the thermosetting epoxy resin comprises bisphenol A type epoxy resin.
[0040] Preferably, the degree of polymerization of the thermosetting epoxy resin is 10-20, for example, the degree of polymerization may be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, the curing agent comprises any one of m-phenylenediamine, ethylenediamine or polyamide or a combination of at least two thereof, typical but non-limiting combinations include phenylenediamine and ethylenediamine, phenylenediamine and polyamide, ethylenediamine and polyamide, and phenylenediamine, ethylenediamine and polyamide, preferably m-phenylenediamine.
[0042] Preferably, the process of pressing the NdFeB magnet powder to obtain the NdFeB magnet green body also includes adding a lubricant.
[0043] Preferably, the lubricant comprises any one or a combination of at least two of olive oil, graphite or oxidized polyethylene wax. Typical but non-limiting combinations include olive oil and graphite, olive oil and oxidized polyethylene wax, graphite and oxidized polyethylene wax, and olive oil, graphite and oxidized polyethylene wax, preferably graphite.
[0044] Preferably, the method for preparing the adhesive comprises: dispersing the thermosetting epoxy resin and the curing agent in a solvent to obtain the adhesive.
[0045] Preferably, the mass of the solvent is 1-4 times the total mass of the thermosetting epoxy resin and the curing agent, for example, it can be 1, 2, 3 or 4 times, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the solvent comprises any one of acetone, propylene oxide, ethyl acetate or xylene, or a combination of at least two thereof. Typical but non-limiting combinations include acetone and propylene oxide, acetone and ethyl acetate, acetone and xylene, propylene oxide and ethyl acetate, propylene oxide and xylene, ethyl acetate and xylene, acetone, propylene oxide and ethyl acetate, acetone, propylene oxide and xylene, propylene oxide, ethyl acetate and xylene, and acetone, propylene oxide, ethyl acetate and xylene.
[0047] Preferably, the method for preparing the magnetic powder comprises: ball milling the NdFeB powder and semi-metallic ferrimagnetic powder to obtain the magnetic powder.
[0048] Preferably, the frequency of the ball milling is 5-10 Hz, for example, 5 Hz, 5.5 Hz, 6 Hz, 6.5 Hz, 7 Hz, 7.5 Hz, 8 Hz, 8.5 Hz, 9 Hz, 9.5 Hz or 10 Hz, including but not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0049] Preferably, the ball milling time is 1-10 h, for example, it can be 1 h, 1.5 h, 2 h, 5.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, 8.5 h, 9 h, 9.5 h or 10 h, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the method of mixing the binder and the magnetic powder includes stirring.
[0051] Preferably, the stirring speed is 100-300rpm, for example, it can be 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm, 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm or 300rpm, including but not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0052] Preferably, the stirring time is 15-30 min, for example, it can be 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In the present invention, the magnetic powder and the binder are mixed and then dried in order to completely volatilize the organic solvent in the system.
[0054] Preferably, the drying temperature is 60-90°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] Preferably, after the drying, before pressing the NdFeB magnet powder to obtain a NdFeB magnet green body, the process further includes screening the NdFeB magnet powder.
[0056] Preferably, the screening is carried out by using a sieve.
[0057] Preferably, the mesh number of the sieve is 400-600 mesh, for example, it can be 400 mesh, 410 mesh, 420 mesh, 430 mesh, 440 mesh, 450 mesh, 460 mesh, 470 mesh, 480 mesh, 490 mesh, 500 mesh, 510 mesh, 520 mesh, 530 mesh, 540 mesh, 550 mesh, 560 mesh, 570 mesh, 580 mesh, 590 mesh or 600 mesh, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] Preferably, the curing temperature is 150°C-200°C, for example, it can be 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C or 200°C, including but not limited to the listed values, and other unlisted values within the numerical range are also applicable, preferably 180-200°C.
[0059] Preferably, the curing time is 40 min-80 min, for example, it can be 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min, 60 min, 62 min, 64 min, 66 min, 68 min, 70 min, 72 min, 74 min, 76 min, 78 min or 80 min, including but not limited to the listed values, other unlisted values within the numerical range are also applicable, preferably 40 min-60 min.
[0060] Preferably, in the NdFeB magnet green body, the mass ratio of NdFeB powder, semi-metallic ferrimagnetic powder, binder and lubricant is 100:(3-15):(2-7):(0.5-1), for example, it can be 100:3:2:0.5, 100:4:2.5:0.55, 100:5:3:0.6, 100:6:3.5:0.65, 100:7:3.8:0.68, 100:8:4:0.7, 100:9:4.3:0.72, 100:10:4.5:0.75, 100:11:5:0.8, 100:12:5.5:0.85, 100:13:6:0.9, 100:14:6.5:0.95, 100:15:7:1, including but not limited to the listed values, other values not listed within the numerical range are also applicable.
[0061] In a third aspect, the present invention provides an application of the bonded NdFeB magnet as described in the first aspect, wherein the bonded NdFeB magnet is applied in a motor or a generator.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] The present invention uses semi-metallic ferrimagnetic powder as a reinforcing phase in a bonded NdFeB magnet. On the one hand, the semi-metallic ferrimagnetic powder belongs to a cubic crystal system and has good energy absorption performance, and can improve the mechanical strength of the bonded NdFeB magnet. On the other hand, the semi-metallic ferrimagnetic powder has high magnetocrystalline anisotropy, and improves the magnetic properties of the bonded NdFeB magnet while improving the mechanical strength of the bonded NdFeB magnet. DETAILED DESCRIPTION
[0064] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0065] Example 1
[0066] This embodiment provides a NdFeB magnet, and the bonded NdFeB magnet is prepared by the following preparation method:
[0067] (1) 3 g of bisphenol A epoxy resin having a degree of polymerization of 15 and 0.3 g of m-phenylenediamine were mixed in 6.6 g of acetone to obtain a binder.
[0068] (2) Use a ball mill to mix 100 g of particles D 50 45μm NdFeB powder with 7.5g particle size D 50 The ball milling frequency is 6 Hz and the ball milling time is 5 h to obtain mixed magnetic powder.
[0069] (3) Under a first stirring condition at a rotation speed of 200 rpm, the binder obtained in step (1) and the mixed magnetic powder obtained in step (2) were stirred for 20 minutes, dried at 75° C., and sieved using a 500-mesh sieve to obtain NdFeB magnet powder.
[0070] (4) During the second stirring, 0.5 g of graphite is mixed with the NdFeB magnet powder obtained in step (3), and the mixture is pressed to obtain a NdFeB magnet green body; the mass ratio of the NdFeB powder, the semi-metallic ferrimagnet powder, the binder and the lubricant in the obtained NdFeB magnet green body is 100:7.5:3.3:0.5.
[0071] (5) Curing the NdFeB magnet green body obtained in step (4) at 180° C. for 50 min to obtain the bonded NdFeB magnet.
[0072] Example 2
[0073] This embodiment provides a bonded NdFeB magnet, which is prepared by the following preparation method:
[0074] (1) 5 g of a glycidyl ester epoxy resin having a degree of polymerization of 10 and 0.8 g of ethylenediamine were mixed in 5.8 g of xylene to obtain a binder.
[0075] (2) Use a ball mill to mix 100 g of particle size D 50 10g of NdFeB powder with a particle size of 30μm 50 The ball milling frequency is 5 Hz, the ball milling time is 10 h, and mixed magnetic powder is obtained.
[0076] (3) Under a first stirring condition at a rotation speed of 100 rpm, the binder obtained in step (1) and the mixed magnetic powder obtained in step (2) were stirred for 15 minutes, dried at 60° C., and sieved using a 400-mesh sieve to obtain NdFeB magnet powder.
[0077] (4) During the second stirring, 0.8 g of olive oil is mixed with the NdFeB magnet powder obtained in step (3), and the mixture is pressed to obtain a NdFeB magnet green body; the mass ratio of the NdFeB powder, the semi-metallic ferrimagnet powder, the binder and the lubricant in the obtained NdFeB magnet green body is 100:10:5.8:0.8.
[0078] (5) Curing the NdFeB magnet green body obtained in step (4) at 150° C. for 80 min to obtain the bonded NdFeB magnet.
[0079] Example 3
[0080] This embodiment provides a bonded NdFeB magnet, which is prepared by the following preparation method:
[0081] (1) 2 g of bisphenol A type epoxy resin having a degree of polymerization of 13 and 0.2 g of m-phenylenediamine were mixed with 6.9 g of propylene oxide to obtain a binder.
[0082] (2) Use a ball mill to mix 100 g of particle size D 50 40μm NdFeB powder with 5g particle size D 50 The particle size of Pb2CrReO6 is 18 μm, the ball milling frequency is 10 Hz, the ball milling time is 1 h, and mixed magnetic powder is obtained.
[0083] (3) Under a first stirring condition at a rotation speed of 300 rpm, the binder obtained in step (1) and the mixed magnetic powder obtained in step (2) were stirred for 25 minutes, dried at 85° C., and sieved using a 550-mesh sieve to obtain NdFeB magnet powder.
[0084] (4) During the second stirring, 0.7 g of graphite is mixed with the NdFeB magnet powder obtained in step (3), and the mixture is pressed to obtain a NdFeB magnet green body; the mass ratio of the NdFeB powder, the semi-metallic ferrimagnet powder, the binder and the lubricant in the obtained NdFeB magnet green body is 100:5:2.2:0.7.
[0085] (5) Curing the NdFeB magnet green body obtained in step (4) at 170° C. for 60 min to obtain the bonded NdFeB magnet.
[0086] Example 4
[0087] This embodiment provides a bonded NdFeB magnet, which is prepared by the following preparation method:
[0088] (1) mixing 7 g of bisphenol A epoxy resin having a degree of polymerization of 20 and 1.4 g of polyamide in 32 g of ethyl acetate to obtain a binder;
[0089] (2) Use a ball mill to mix 100 g of particle size D 50 60μm NdFeB powder with 7.5g particle size D 50 The Sr2FeReO6 with a particle size of 25 μm was milled at a frequency of 7.5 Hz and a milling time of 8 h to obtain mixed magnetic powder.
[0090] (3) stirring the binder obtained in step (1) and the mixed magnetic powder obtained in step (2) for 30 minutes at a first stirring speed of 250 rpm, drying at 90° C., and sieving with a 600-mesh sieve to obtain NdFeB magnet powder;
[0091] (4) During the second stirring, 1 g of oxidized polyethylene wax is mixed with the NdFeB magnet powder obtained in step (3), and the mixture is pressed to obtain a NdFeB magnet green body; the mass ratio of the NdFeB powder, the semi-metallic ferrimagnet powder, the binder and the lubricant in the obtained NdFeB magnet green body is 100:7.5:8.4:1.
[0092] (5) Curing the NdFeB magnet green body obtained in step (4) at 200° C. for 40 minutes to obtain the bonded NdFeB magnet.
[0093] Example 5
[0094] This embodiment provides a bonded NdFeB magnet, which is the same as Example 1 except that the mass of Pb2CrReO6 is adjusted to 3g, that is, the mass ratio of NdFeB powder, semi-metallic ferrimagnetic powder, binder and lubricant in the obtained NdFeB magnet green body is 100:3:3.3:0.5.
[0095] Example 6
[0096] This embodiment provides a bonded NdFeB magnet, which is the same as Example 1 except that the mass of Pb2CrReO6 is adjusted to 15g, that is, the mass ratio of NdFeB powder, semi-metallic ferrimagnetic powder, binder and lubricant in the obtained NdFeB magnet green body is 100:15:3.3:0.5.
[0097] Example 7
[0098] The present embodiment provides a bonded NdFeB magnet, which is the same as that in Embodiment 1 except that the mass of the thermosetting epoxy resin is adjusted to 1 g and the mass of the curing agent is adjusted to 0.1 g, that is, the mass ratio of NdFeB powder, semi-metallic ferrimagnetic powder, binder and lubricant in the obtained NdFeB magnet green body is 100:7.5:1.1:0.5.
[0099] Example 8
[0100] This embodiment provides a bonded NdFeB magnet, which is the same as Example 1 except that the mass of the thermosetting epoxy resin is adjusted to 8 g and the mass of the curing agent is adjusted to 0.8 g, that is, the mass ratio of NdFeB powder, semi-metallic ferrimagnetic powder, binder and lubricant in the obtained NdFeB magnet green body is 100:7.5:8.8:0.5.
[0101] Comparative Example 1
[0102] This comparative example provides a bonded NdFeB magnet, which is the same as Example 1 except that Pb2CrReO6 is not added.
[0103] Comparative Example 2
[0104] This comparative example provides a bonded NdFeB magnet, which is the same as Example 1 except that Pb2CrReO6 is replaced by 304 stainless steel powder of the same mass and equivalent particle size.
[0105] Comparative Example 3
[0106] This comparative example provides a bonded NdFeB magnet, which is the same as Example 1 except that Pb2CrReO6 is replaced by alumina ceramic powder of the same mass and equivalent particle size.
[0107] Performance Test:
[0108] The flexural strength and fracture toughness of the bonded NdFeB magnets obtained in Examples 1 to 8 and Comparative Examples 1 and 2 were tested by a three-point bending test and a SENB method, respectively, and their magnetic properties were measured by a vibrating sample magnetometer. The test results are shown in Table 1.
[0109] Table 1
[0110]
[0111]
[0112] According to the data of Examples 1 to 8 of the present invention and the data results of Comparative Example 1, it can be seen that after adding the semi-metallic ferrimagnetic powder, the bending strength and tear toughness of the bonded NdFeB magnet are significantly improved, and the remanence is also improved at the same time, that is, the simultaneous improvement of mechanical properties and magnetic properties is achieved.
[0113] According to the data results of Example 1 and Example 5-Example 6, the semi-metallic ferrimagnetic powder of the appropriate mass ratio is dispersed between the NdFeB powders, so that the arrangement between the phases is more closely and regularly arranged. Thanks to the crystal structure of the semi-metallic ferrimagnetic powder, the bending strength of the magnet is greatly improved, and the tear toughness is also improved. At the same time, due to the high magnetocrystalline anisotropy of the semi-metallic ferrimagnetic powder, the residual magnetic properties of the bonded NdFeB magnet are also improved. Too much or too little semi-metallic ferrimagnetic powder reduces the bending resistance, tear toughness and residual magnetic improvement effect of the bonded NdFeB magnet, which is attributed to the fact that too much semi-metallic ferrimagnetic powder occupies too many gaps, destroying the close relationship between the original NdFeB powders, while too little semi-metallic ferrimagnetic powder cannot fully fill the gaps between the NdFeB, resulting in unsatisfactory improvement effects on mechanical properties and magnetic properties.
[0114] According to the data results of Example 1 and Example 7-Example 8, too much or too little thermosetting epoxy resin will also lead to unsatisfactory improvement effects on the mechanical and magnetic properties of the bonded NdFeB magnet.
[0115] According to the data results of Example 1 and Comparative Examples 2-3, after replacing the semi-metallic ferrimagnetic powder in the present invention with stainless steel powder or alumina ceramic powder of equal mass and equivalent particle size, the mechanical strength of the bonded NdFeB magnet is not as improved as that of the present invention, and the introduction of stainless steel powder or alumina ceramic powder also leads to a decrease in the magnetic properties of the bonded NdFeB magnet.
[0116] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A bonded NdFeB magnet, characterized in that: The bonded NdFeB magnet comprises NdFeB powder and semi-metallic ferrimagnet powder; The mass ratio of the NdFeB powder to the semi-metallic ferrimagnetic powder is 100:(3-15).
2. The bonded NdFeB magnet according to claim 1, wherein: The semi-metallic ferrimagnetic powder includes perovskite semi-metallic ferrimagnetic powder; Preferably, the perovskite semi-metallic ferrimagnetic powder comprises any one of Pb2CrReO6, Ba2FeReO6 or Sr2FeReO6 or a combination of at least two thereof; Preferably, the perovskite semi-metallic ferrimagnetic powder is Pb2CrReO6.
3. The bonded NdFeB magnet according to claim 1 or 2, characterized in that: The particle size D of the NdFeB powder 50 30-60 μm, preferably 30-45 μm; Preferably, the particle size D of the semi-metallic ferrimagnetic powder is 50 15-25μm.
4. The bonded NdFeB magnet according to any one of claims 1 to 3, characterized in that: The mass ratio of the NdFeB powder to the semi-metallic ferrimagnetic powder is 100:(5-10); Preferably, the NdFeB magnet also includes a binder and a lubricant; Preferably, the adhesive comprises a thermosetting epoxy resin and a curing agent.
5. The bonded NdFeB magnet according to claim 4, characterized in that: The thermosetting epoxy resin includes any one of bisphenol A epoxy resin, bisphenol S epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, novolac epoxy resin, brominated epoxy resin, glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin or alicyclic epoxy resin, or a combination of at least two thereof; Preferably, the thermosetting epoxy resin comprises bisphenol A epoxy resin; Preferably, the degree of polymerization of the thermosetting epoxy resin is 10-20; Preferably, the curing agent comprises any one or a combination of at least two of m-phenylenediamine, ethylenediamine or polyamide, preferably m-phenylenediamine; Preferably, the lubricant includes any one of olive oil, graphite or oxidized polyethylene wax, or a combination of at least two thereof, preferably graphite.
6. The bonded NdFeB magnet according to claim 4 or 5, characterized in that: In the bonded NdFeB magnet, the mass ratio of the NdFeB powder to the binder is 100:(2-7), preferably 100:(3-5.5); Preferably, the mass ratio of the NdFeB powder to the lubricant is 100:(0.5-1); Preferably, the mass ratio of the thermosetting epoxy resin to the curing agent in the adhesive is 1:(0.1-0.2).
7. A method for preparing a bonded NdFeB magnet according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Mixing magnetic powder and the binder, drying to obtain NdFeB magnet powder; pressing the NdFeB magnet powder to obtain a NdFeB magnet green body; curing the NdFeB magnet green body to obtain the bonded NdFeB magnet; The magnetic powder includes neodymium iron boron powder and semi-metallic ferrimagnetic powder.
8. The preparation method according to claim 7, characterized in that: The adhesive comprises a thermosetting epoxy resin and a curing agent; Preferably, the mass ratio of the thermosetting epoxy resin to the curing agent in the adhesive is 1:(0.1-0.2); Preferably, the thermosetting epoxy resin includes any one or a combination of at least two of bisphenol A epoxy resin, bisphenol S epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, novolac epoxy resin, brominated epoxy resin, glycidyl ether epoxy resin, glycidyl ester epoxy resin, glycidyl amine epoxy resin or alicyclic epoxy resin; Preferably, the thermosetting epoxy resin comprises bisphenol A epoxy resin; Preferably, the degree of polymerization of the thermosetting epoxy resin is 10-20; Preferably, the curing agent comprises any one or a combination of at least two of m-phenylenediamine, ethylenediamine or polyamide, preferably m-phenylenediamine; Preferably, the process of pressing the NdFeB magnet powder to obtain the NdFeB magnet green body further includes adding a lubricant; Preferably, the lubricant comprises any one of olive oil, graphite or oxidized polyethylene wax or a combination of at least two thereof, preferably graphite; Preferably, the preparation method of the adhesive comprises: dispersing the thermosetting epoxy resin and the curing agent in a solvent to obtain the adhesive; Preferably, the mass of the solvent is 1-4 times the total mass of the thermosetting epoxy resin and the curing agent; Preferably, the solvent comprises any one of acetone, propylene oxide, ethyl acetate or xylene, or a combination of at least two thereof; Preferably, the method for preparing the magnetic powder comprises: ball milling the NdFeB powder and the semi-metallic ferrimagnetic powder to obtain the magnetic powder; Preferably, the frequency of the ball milling is 5-10 Hz; Preferably, the ball milling time is 1-10h; Preferably, the method of mixing the binder and the magnetic powder includes stirring; Preferably, the stirring speed is 100-300 rpm; Preferably, the stirring time is 15-30 min; Preferably, after the drying, before pressing the NdFeB magnet powder to obtain a NdFeB magnet green body, the process further includes screening the NdFeB magnet powder; Preferably, the screening method is screening using a sieve; Preferably, the mesh size of the sieve is 400-600 mesh; Preferably, the curing temperature is 150°C-200°C, preferably 180-200°C; Preferably, the curing time is 40 min-80 min, preferably 40 min-60 min.
9. The preparation method according to claim 8, characterized in that: In the NdFeB magnet green body, the mass ratio of NdFeB powder, semi-metallic ferrimagnetic powder, binder and lubricant is 100:(3-15):(2-7):(0.5-1).
10. An application of the bonded NdFeB magnet according to any one of claims 1 to 6, characterized in that: The bonded NdFeB magnet is used in a motor or a generator.
Citation Information
Patent Citations
High-magnetism high-mechanical-strength bonded neodymium iron boron (NdFeB) permanent magnet and preparation method thereof
CN102938283A
Preparation method for high-performance bonded neodymium iron boron permanent magnet material
CN106384639A
High-performance bonded neodymium-iron-boron magnet and preparing method thereof
CN106816251A